An abattoir survey of equine dental abnormalities in Queensland, Australia. Issue 6 (June 2015) - Chinkangsadarn, T; Wilson, GJ; Greer, RM; Pollitt, CC; Bird, PS
<x xml:space="preserve">Abstract</x> Objective A cadaver study to estimate the prevalence of dental disorders in horses presented at an abattoir in Queensland, Australia. Methods Cadaver heads at a Queensland abattoir were examined for the presence of dental abnormalities and categorised into age groups. The prevalence of abnormalities was analysed by binomial observation of observed proportion, Pearson's Chi‐square test or Fisher's exact correlation test. Strength of association was evaluated using Cramer's V test. Results Heads from horses (n = 400) estimated to be between 1 and 30 years of age were placed into four age groups. The most common abnormalities were sharp enamel points (55.3%) and hooks (43%). The highest frequency of dental diseases and abnormalities were in horses 11–15 years old (97.5%). Conclusions Common abnormalities were found in all groups and the prevalence increased with age. This study suggests that all horses should have regular complete dental examinations to detect and treat dental disorders in order to limit more severe dental pathologies later in life.